2007
DOI: 10.1507/endocrj.kr-78
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles of Rab27 Effectors in Regulated Exocytosis

Abstract: Abstract. Recent discoveries that Rab27a/b and their multiple effectors are involved in the regulated exocytosis of lysosome-related organelles and secretory granules have generated numerous related studies. However, not all of these studies have yielded physiologically relevant data because they were not all performed under physiological conditions. For example, "in vivo interactions" have been claimed without examination of the endogenous complex. In some studies, the only proof of interaction was between ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 65 publications
2
42
0
1
Order By: Relevance
“…Furthermore, mice deficient in these proteins exhibit defects in granule biogenesis and/or maturation (Cao et al, 2013;Holst et al, 2013). On the other hand, Rab27a associates with secretory granules (Yi et al, 2002) and regulates the late steps of granule exocytosis, such as recruitment and/or docking to fusion sites, through its multiple effector proteins (Izumi, 2007(Izumi, , 2011. Consistent with this, we found that knockdown of Rab2a or ICA69 inhibits insulin synthesis and processing, whereas that of Rab27a primarily affects insulin secretion.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, mice deficient in these proteins exhibit defects in granule biogenesis and/or maturation (Cao et al, 2013;Holst et al, 2013). On the other hand, Rab27a associates with secretory granules (Yi et al, 2002) and regulates the late steps of granule exocytosis, such as recruitment and/or docking to fusion sites, through its multiple effector proteins (Izumi, 2007(Izumi, , 2011. Consistent with this, we found that knockdown of Rab2a or ICA69 inhibits insulin synthesis and processing, whereas that of Rab27a primarily affects insulin secretion.…”
Section: Discussionsupporting
confidence: 81%
“…7E). However, suppression of Rab27a, a Rab GTPase involved in exocytosis of lysosome-related organelles and secretory granules (Izumi 2007), had little effect on lumen formation in the cyst assay (Fig. 7C).…”
Section: Inhibition Of Apical Transport Partially Recapitulates Cdx2-mentioning
confidence: 99%
“…dense cored secretory granules in PC12 cells, and late endosome/lysosome related secretory granules e.g. melanosomes in melanocytes, lytic granules in T lymphocytes, MIIC in dendritic cells (Izumi, 2007). Using a semi-quantitative FACS-based assay of exosome secretion from HeLa cells stably expressing transactivator CIITA (an activator of the MHC class II family genes, including HLA-DR-marker of exosomes) and a secreted form of chicken ovalbumin (marker of the constitutive secretory pathway), they found that RNAi knockdown of several Rabs, including Rab27A and Rab27B, resulted in a specific reduction in exosome secretion.…”
Section: Rab Proteins and Exosome Biogenesis And Secretionmentioning
confidence: 99%